2023
DOI: 10.1088/1361-665x/acbdd5
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of LPBF for producing Cu-11Al-5Ni-4Fe wt.% with shape memory properties

Abstract: The Cu-11Al-5Ni-4Fe wt% alloy was consolidated by additive manufacturing (AM) to determine the method applicability for producing shape memory alloy. The alloy was researched through compressive stress in three conditions: commercial (cast), as-built, and as-built heat treated (quenched). The results demonstrated that the as-built sample acquired a reasonable superelasticity at room temperature (~4%), which was improved to 6% after quenching. The commercial sample damping capacity was better at high temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Guerra et al [5] demonstrated the applicability of Cu-11Al-5Ni-4Fe wt% for producing shape memory alloy by additive manufacturing. Compressive stress testing was performed on the alloy in three different states: as-built (AB), heat treated (AB), and commercial (COM) (cast) (quenched).…”
mentioning
confidence: 99%
“…Guerra et al [5] demonstrated the applicability of Cu-11Al-5Ni-4Fe wt% for producing shape memory alloy by additive manufacturing. Compressive stress testing was performed on the alloy in three different states: as-built (AB), heat treated (AB), and commercial (COM) (cast) (quenched).…”
mentioning
confidence: 99%